The Donut Chef - Staake, Bob. (New York Golden Books, 2008)
In this delicious tale, a baker hangs out his shingle on a small street and soon the line for his donuts stretches down the block. But it's not long before the competition arrives and a battle of the bakers ensues.
K - 2
Keywords: 1. Baking - Fiction; 2. Donuts - Fiction